Research directions in plant protection chemistry - Andras Szekacs; Tamas Komives (Ecocycles, 2017)
This Opinion paper briefly summarizes the views of the authors on the directions of research in the area of plant protection chemistry. We believe these directions need to focus on (1) the discovery of new pesticide active ingredients, and (2) the protection of human health and the environment. Research revenues are discussed thematically in topics of target site identification, pesticide discovery, environmental aspects, as well as keeping track with the international trends. The most fundamental approach, target site identification, covers both computer-aided molecular design and research on biochemical mechanisms. The discovery of various classes of pesticides is reviewed including classes that hold promise to date, as well as up-to-date methods of innovation, e.g. utilization of plant metabolomics in identification of novel target sites of biological activity. Environmental and ecological aspects represent a component of increasing importance in pesticide development by emphasizing the need to improve methods of environmental analysis and assess ecotoxicological side-effects, but also set new directions for future research. Last, but not least, pesticide chemistry and biochemistry constitute an integral part in the assessment of related fields of plant protection, e.g. agricultural biotechnology, therefore, issues of pesticide chemistry related to the development and cultivation of genetically modified crops are also discussed.